Evaluation of CSF1R‐related adult onset leukoencephalopathy with axonal spheroids and pigmented glia diagnostic criteria. (28th September 2021) - Ayrignac, Xavier; Carra‐Dallière, Clarisse; Codjia, Pekes; Mouzat, Kevin; Castelnovo, Giovanni; Ellie, Emmanuel; Etcharry‐Bouyx, Frédérique; Belliard, Serge; Marelli, Cecilia; Portet, Florence; Le Ber, Isabelle; Durand‐Dubief, Francoise; et al.
Abstract: Background and purpose: Diagnostic criteria for adult onset leukoencephalopathy with axonal spheroids and pigmented glia (ALSP) due to colony‐stimulating factor 1 receptor ( CSF1R ) mutation have recently been proposed. Our objective was to assess their accuracy in an independent multicenter cohort. Methods: We evaluated the sensitivity and specificity of the diagnostic criteria for ALSP (including the "probable" and "possible" definitions) in a national cohort of 22 patients with CSF1R mutation, and 59 patients with an alternative diagnosis of adult onset inherited leukoencephalopathy. Results: Overall, the sensitivity of the diagnostic criteria for ALSP was 82%, including nine of 22 patients diagnosed as probable and nine of 22 diagnosed as possible. Twenty of the 59 CSF1R mutation‐negative leukoencephalopathies fulfilled the diagnostic criteria, leading to a specificity of 66%. Conclusions: Diagnostic criteria for ALSP have an overall limited sensitivity along with a modest specificity. We suggest that in patients suspected of genetic leukoencephalopathy, a comprehensive magnetic resonance imaging pattern‐based approach is warranted, together with white matter gene panel or whole exome sequencing. Abstract : Adult onset leukoencephalopathy with axonal spheroids and pigmented glia (ALSP) is due to heterozygous CSF1R mutations. It is increasingly recognized as a major cause of inherited leukoencephalopathies in adulthood. Our study assessed the sensitivity and specificity of diagnostic criteria for ALSP and suggests that they may be misleading. Instead, we propose that every patient with an unexplained rapidly evolving leukoencephalopathy should be tested for a CSF1R mutation, as a potential therapy (allogenic hematopoietic stem cell transplantation) exists.